The Impact of Climate Change on Pavement Temperatures and Asphalt Binder Grade Selection in Estonia Based on Different Climate Change Scenarios - Karli Kontson; Kristjan Lill; Artu Ellmann; Andrus Aavik (The Baltic Journal of Road and Bridge Engineering)
This paper examines the impact of climate change on asphalt pavement temperatures and Superpave asphalt binder Performance Grade (PG) selection in Estonia. Pavement temperatures were estimated using statistical-empirical pavement temperature prediction models tailored for Estonian conditions. The impact of climate change on pavement temperatures was assessed based on the latest climate change models, assuming three different climate change scenarios for the near, medium and long terms. Projected changes reflect warming trends, with both coastal and mainland areas experiencing substantial shifts in binder grades. Asphalt binder low temperature PG grades are more significantly influenced by climate change, leading to narrower pavement temperature ranges in the region.